2012
DOI: 10.4171/jems/329
|View full text |Cite
|
Sign up to set email alerts
|

Skew-symmetric cluster algebras of finite mutation type

Abstract: In the famous paper [FZ2] Fomin and Zelevinsky obtained Cartan-Killing type classification of all cluster algebras of finite type, i.e. cluster algebras having only finitely many distinct cluster variables. A wider class of cluster algebras is formed by cluster algebras of finite mutation type which have finitely many exchange matrices (but are allowed to have infinitely many cluster variables). In this paper we classify all cluster algebras of finite mutation type with skew-symmetric exchange matrices. Beside… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
178
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(178 citation statements)
references
References 8 publications
0
178
0
Order By: Relevance
“…In this paper we use more combinatorial methods for more general diagrams. Let us also mention that there are algorithms to check whether a given skew-symmetric matrix is of finite mutation type: one of them is realized in B. Keller's computer program (which is available at www.math.jussieu.fr/~keller/quivermutation); a polynomial-time algorithm is given in [7].…”
Section: Theorem 33 Let S Be a Mutation Class Of Connected Diagramsmentioning
confidence: 99%
“…In this paper we use more combinatorial methods for more general diagrams. Let us also mention that there are algorithms to check whether a given skew-symmetric matrix is of finite mutation type: one of them is realized in B. Keller's computer program (which is available at www.math.jussieu.fr/~keller/quivermutation); a polynomial-time algorithm is given in [7].…”
Section: Theorem 33 Let S Be a Mutation Class Of Connected Diagramsmentioning
confidence: 99%
“…These cluster algebras represent three of the 11 exceptional mutation finite cluster algebras with skew symmetric exchange matrix [8] and one is the surface algebra corresponding to the 4-punctured sphere. Figure 1 shows representatives of their exchange matrices in quiver form.…”
Section: Introductionmentioning
confidence: 99%
“…We say that a matrix B (and the corresponding cluster algebra) is mutation finite (or is of finite-mutation type) if its mutation-equivalence class is finite, i.e., only finitely many matrices can be obtained from B by repeated matrix mutations. Felikson, Shapiro, and Tumarkin gave a classification of all skew-symmetric mutation-finite cluster algebras in [7]. They showed that these cluster algebras are the union of the following classes of cluster algebras:…”
Section: Applications Of Teichmüller Theory To Cluster Theorymentioning
confidence: 99%